Translation of German and English Human-Denoting Compound Nouns into Russian. (13th May 2015) - Ivanova, Tatiana; Arzhantseva, Natalia
Abstract: The authors provide a comparative analysis of human-denoting compound nouns in the word-building systems of the German, English and Russian languages. The analysis of the given group of words is carried out on the onomasiological basis pursuing the goal of revealing general and specific tendencies in the development of the given word-building categories of kindred and non-kindred languages. The qualitative and quantitative analysis of the given phenomena is aimed at revealing the general tendencies in the word-building system of human-denoting compound nouns (especially names of a man as a doer of an action) in the German, English and Russian languages, and also the regularities of their translation in the contrastive aspect. Among the word-building types the authors have singled out general and specific word-building meanings compound nouns of the given languages possess. Having analyzed the word-building meanings the authors single out two groups of compound human-denoting nouns (compound nouns based on action, compound nouns based on an attribute) and carry out their structural and semantic analysis to reveal the regularities of word-building of complex lexical units and their further translation. The authors also provide a table summarizing the received results.